"The nuclear envelope, a meiotic jack-of-all-trades". (June 2020) - Zetka, Monique; Paouneskou, Dimitra; Jantsch, Verena
Abstract: The nucleus is one of the membrane-bound organelles that are a distinguishing feature between eukaryotes and prokaryotes. During meiosis, the nuclear envelope takes on functions beyond separating the nucleoplasm from the cytoplasm. These include associations with meiotic chromosomes to mediate pairing, being a sensor for recombination progression, and supportive of enormous nuclear growth during oocyte formation. In this review, we highlight recent results that have contributed to our understanding of meiotic nuclear envelope function and dynamics.